The effect of low temperatures on the fatigue crack growth of S460 structural steel: - Walters, C.L.; Alvaro, A.; Maljaars, J. (2016)
The Fatigue Ductile–Brittle Transition (FDBT) is a phenomenon similar to the fracture ductile to brittle transition, in which the fracture mode of the fatigue cracks changes from ductile transgranular to cleavage and/or grain boundary separation. Fatigue at temperatures below the FDBT has a much different crack growth rate than fatigue above that temperature. In an attempt to give practical guidance as to whether or not the FDBT is relevant for design, this paper compares a FDBT curve to the much more common Charpy and CTOD transition curves for an S460 structural steel. The data in this paper suggests that choosing a steel with a Charpy energy in Joules greater than 10% of its yield strength in MPa at the design temperature may not be adequate to assure that a fatigue ductile to brittle transition does not occur in service conditions